ANALYSIS OF CONSUMER AND BUSINESS CONFIDENCE, EXPORTS, AND GOVERNMENT EXPENDITURE RELATED TO ECONOMIC GROWTH IN ASIA - Vicri Rahmatin Qadri; Sri Indah Nikensari; Suparno Suparno (Yayasan Education and Social Center, 2022)
Economic growth is still the main indicator to see the development of economic activity. This study aims to determine the effect of consumer confidence, business confidence, government spending, and exports on economic growth in Asian countries, before the Covid pandemic occurred. Panel data were collected during the period 2015 - 2019 in Asian countries, which were analyzed using multiple linear regression equations. The results show that all the proposed variables have a positive effect on economic growth in Asia, except for the Government Expenditure factor. These results also show that before the Covid pandemic, consumer confidence, business confidence and exports in each country still contributed to economic growth, although based on the determination test, only 50.27% of these variables explained the movement of economic growth in Asia